INTERVENSI STIMULASI MOTORIK, AFEKTIF, DAN KOGNITIF PADA ANAK DENGAN DOWN SYNDROME : A NARRATIVE REVIEW - Wiwi Mardiah (Bajang Institute, 2022)
The number of children with Down syndrome in Indonesia in 2018 reached 0.21% with the highest prevalence in West Java, which is around 50.90%. One of the problems in children with Down syndrome is limitations or delays in cognitive, affective and motor development. Objective: This review aims to identify motor, affective, and cognitive stimulation interventions in children with Down syndrome. Method: The method used is a narrative review approach. The search strategy used four databases, namely PubMed, CINAHL, and Scholar. In formulating keywords the researcher uses Boolean. Results: Based on the search results obtained 15 articles that meet the criteria. Conclusion: Some of the interventions that can be done include playing engklek, bocce, throwing a ball at the target, compiling puzzles, making mosaic art, VR, MUTALAGI, DSL+, and occupational therapy.